2020
DOI: 10.3389/fonc.2020.581037
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Analysis of Qualitative MR Imaging Features for the Differentiation of Glioblastoma and Brain Metastases

Abstract: ObjectivesTo identify qualitative VASARI (Visually AcceSIble Rembrandt Images) Magnetic Resonance (MR) Imaging features for differentiation of glioblastoma (GBM) and brain metastasis (BM) of different primary tumors.Materials and MethodsT1-weighted pre- and post-contrast, T2-weighted, and T2-weighted, fluid attenuated inversion recovery (FLAIR) MR images of a total of 239 lesions from 109 patients with either GBM or BM (breast cancer, non-small cell (NSCLC) adenocarcinoma, NSCLC squamous cell carcinoma, small-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Decrease in FLAIR signal in glioblastoma compared with metastasis [10] 44% 91% Dynamic susceptibility contrast perfusion using rCBV [19] 90% 91% Both DWI and DTI [20] 79.8% 80.9% Diffusion tensor imaging using a VEC threshold of 0.48 [21] 100% 83.3% DTI parameters with DSC [22] 60-91% 55-100% 98% MRS with LM13 class lipids and cutoff of 81 mM [23] 81% 78% 85% PET imaging with α [11C] methyl-l-tryptophan with kinetic tracer analysis [24] 93% Machine learning algorithm with MRS and DSC data [25] 98% Two-dimensional morphological feature extraction for DTI [26] 97.9%…”
Section: Imaging Technique Sensitivity Specificity Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Decrease in FLAIR signal in glioblastoma compared with metastasis [10] 44% 91% Dynamic susceptibility contrast perfusion using rCBV [19] 90% 91% Both DWI and DTI [20] 79.8% 80.9% Diffusion tensor imaging using a VEC threshold of 0.48 [21] 100% 83.3% DTI parameters with DSC [22] 60-91% 55-100% 98% MRS with LM13 class lipids and cutoff of 81 mM [23] 81% 78% 85% PET imaging with α [11C] methyl-l-tryptophan with kinetic tracer analysis [24] 93% Machine learning algorithm with MRS and DSC data [25] 98% Two-dimensional morphological feature extraction for DTI [26] 97.9%…”
Section: Imaging Technique Sensitivity Specificity Accuracymentioning
confidence: 99%
“…Tsolaki et al propose a machine learning algorithm that combines MRS data with DSC in the peritumoral area, leading to an accuracy of up to 98% [25]. Yang et al developed a computerized system using a semiautomatic segmentation method for DTI imaging and two-dimensional morphological feature extraction and selection and a pattern recognition module for tumor classification.…”
Section: Radiomics-based Machine Learningmentioning
confidence: 99%
“…Radiomics convert digital medical images into mineable high-dimensional data and have been widely recognized as a practical alternative for noninvasive diagnosis/prognosis in oncology [ 13 , 30 ]. Previous studies demonstrated the feasibility of applying radiomics models to differentiate GBM from SBM based on either conventional MR images or advanced MR technologies [ 4 , 17 , 20 , 22 , 31 ]. Notably, one crucial and defining step for radiomics modeling is the delineation of the lesion VOI.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cases of solitary brain metastasis (SBM), differentiating the GBM from SBM solely based on conventional characteristics on magnetic resonance imaging (MRI) remains challenging. GBM and SBM often share similar radiological manifestations, such as an intratumoral necrotic center and heterogeneous enhancement of the component surrounded by peritumoral edema regions [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation